1962
DOI: 10.1113/jphysiol.1962.sp006893
|View full text |Cite
|
Sign up to set email alerts
|

Volume changes in frog muscle during contraction

Abstract: The variation in volume when a muscle contracts was the subject of much discussion towards the end of the 17th century, and more recently by Fulton (1926) and by Ernst (1958). Many scholars expected an increase in volume as the vital spirits moved from the nerve into the muscle and induced activation: but Swammerdam (ca. 1660) experimented with an isolated muscle contained in a jar with a fine-bore tube attached and in fact observed a slight decrease in volume. Ernst (1925) first demonstrated the decrease with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
2

Year Published

1972
1972
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 5 publications
(5 reference statements)
4
28
2
Order By: Relevance
“…The present finding that glycerol disruption abolishes the LR in single fibres or whole muscle makes it unlikely that the LR can arise in the sarcolemma as suggested by Hill (1951). Furthermore, his proposal that this structure might expand longitudinally is not supported by the present finding that Rmax is not corre-351 LOUIS A. MULIERI lated with Iref* The latter observation also argues against proposals attributing the LR to the early myoplasmic volume changes that occur during the latent period (Abbott & Baskin, 1962;Davies, 1963;Baskin & Paolini, 1966;Peachey, 1968). Since a fibre with more sarcomeres in series, i.e.…”
Section: Discussioncontrasting
confidence: 56%
“…The present finding that glycerol disruption abolishes the LR in single fibres or whole muscle makes it unlikely that the LR can arise in the sarcolemma as suggested by Hill (1951). Furthermore, his proposal that this structure might expand longitudinally is not supported by the present finding that Rmax is not corre-351 LOUIS A. MULIERI lated with Iref* The latter observation also argues against proposals attributing the LR to the early myoplasmic volume changes that occur during the latent period (Abbott & Baskin, 1962;Davies, 1963;Baskin & Paolini, 1966;Peachey, 1968). Since a fibre with more sarcomeres in series, i.e.…”
Section: Discussioncontrasting
confidence: 56%
“…During an isometric or isotonic tetanus all authors have observed a small decrease in the muscle volume of about 0-005 %. During an isometric twitch of skeletal muscle Abbott & Baskin (1962) observed a smaller decrease in volume of about 0-0005 %. The volume changes measured in this way can only be the result of compression or chemical reactions that result in a smaller volume, such as the break-down of creatine phosphate (Meyerhof, 1947); changes in volume as the result of a shift of water between the extracellular and intracellular spaces will not be detected.…”
Section: Introductionmentioning
confidence: 90%
“…The muscle volume was expected to increase, because the vital spirits were thought to move from the nerve into the muscle to induce activation (for references see Abbott & Baskin, 1962). In about 1660 Swammerdam experimented on an isolated muscle in a fluid-filled chamber and observed a small decrease in muscle volume as indicated by a drop in the level of solution.…”
Section: Introductionmentioning
confidence: 99%
“…However, whether myocardium is incompressible or not has not been well demonstrated. That skeletal muscle is practically incompressible during contraction has been accurately shown (Abott and Baskin 1962). Utilizing a sophisticated technique which permitted the measurement of small, rapid volume changes occurring in a muscle during a twitch, they reported in the sartorius muscle that the transient increase which commences at between 2 and 3 msec after the stimulus is about 2.5 x 10-6 and that the decrease during a twitch is about 5 x 10-6 ml/g.…”
mentioning
confidence: 99%